2014
DOI: 10.1007/s10397-014-0854-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ovarian suspension to round ligament with a resorbable suture to prevent postoperative adhesions in women with ovarian endometrioma: follow-up by transvaginal hydrolaparoscopy

Abstract: The aim of this study was to assess the effect of ovarian suspension to the round ipsilateral ligament with a resorbable suture, performed during laparoscopic surgery for endometrioma, on postoperative ovarian adhesion formation. The tool used to assess this effect was not conventional laparoscopy but outpatient transvaginal hydrolaparoscopy. Fifty women with single ovarian endometrioma were divided in two groups (group A, 24 and group B, 26). All patients underwent laparoscopic ovarian cystectomy for endometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 25 publications
(34 reference statements)
0
21
0
Order By: Relevance
“…Redwine, (2001) proposed TOS to the round ligament after operative laparoscopy for severe endometriosis using 3-0 Vicryl suture in patients with chronic pelvic pain secondary to severe endometriosis (Redwine, 2001). Similarly, Pellicano et al, (2014) reported that suspending the ovary to the ipsilateral round ligament using Vicryl Rapid 2.0 CT-1 needle after excision of an endometrioma resulted in significantly lower rate of postsurgical ovarian adhesion as judged by post- operative transvaginal outpatient hydro-laparoscopy (Pellicano et al, 2014). This technique of suspending the ovary to the round ligament, in theory, carries the risk of adhesion formation between these structures which certainly alters the normal anatomy and in turn may reduce fertility potential during natural attempts at achieving pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Redwine, (2001) proposed TOS to the round ligament after operative laparoscopy for severe endometriosis using 3-0 Vicryl suture in patients with chronic pelvic pain secondary to severe endometriosis (Redwine, 2001). Similarly, Pellicano et al, (2014) reported that suspending the ovary to the ipsilateral round ligament using Vicryl Rapid 2.0 CT-1 needle after excision of an endometrioma resulted in significantly lower rate of postsurgical ovarian adhesion as judged by post- operative transvaginal outpatient hydro-laparoscopy (Pellicano et al, 2014). This technique of suspending the ovary to the round ligament, in theory, carries the risk of adhesion formation between these structures which certainly alters the normal anatomy and in turn may reduce fertility potential during natural attempts at achieving pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…A thorough search of literature revealed that there are only 11 manuscripts and 1 published abstract addressing the safety and efficacy of TOS. There are 8 observational studies (7 manuscripts and 1 published abstract) [Abuzeid M et al, 2002; Quahba et al, 2004; Carbonnel et al 2011; Poncelet et al, 2012; Pellicano et al, 2014; Trehan A and Trehan AK 2014; Abuzeid O et al, 2018, Mitwally et al, 2009], 2 systematic reviews (Pergialiotis et al, 2016; Giampaolino et al, 2018), and 2 prospective randomized control trials (Seracchioli et al, 2014; Hoo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome included the prevalence and the severity of ovarian adhesions after ovarian suspension, defined as the total number of adhesions affecting the ovaries and evaluated by means of transvaginal ultrasound (TVU) [16,22,24À26], laparoscopy (LPS) [22,27,28], or transvaginal hydrolaparoscopy (TV-H-LPS) [29]. The severity of ovarian adhesions was graded using the Operative Laparoscopy Study Group (OLSG) criteria (0, no adhesion; 1, smooth and avascular; 2, dense or vascular; 3, cohesive) and the revised American Fertility Society scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…These 8 studies included 2 RCTs [16,28],1 pilot RCT [15], and 5 NRSs [17,22,26,27,29] (Table 1). The NRSs included 4 retrospective studies [17,22,26,27] and 1 prospective cohort study [29]. A total of 795 patients were examined in the 8 studies.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%